PENDIDIKAN AGAMA KRISTEN DI GEREJA PADA ERA REVOLUSI INDUSTRI 4.0 MENUJU KESEHATAN GEREJA PADA MASA PANDEMI - Aryanto Budiono (JURNAL KADESI, 2021)
Christian religious education is one way to mature the faith of believers as well as a way to nourish a church. A healthy church is a church that will grow. Church growth has a double meaning, namely qualitatively (quality) and quantitatively (quantity, number of congregations). All of that can be measured through the attendance of the congregation in every activity, both on a large scale (worship) and small scale (small group). However, since March - April 2020, the Covid 19 Pandemic occurred which resulted in churches closing their in-person meeting activities and replacing them with online activities. Some churches whose congregations are technologically savvy must find ways so that ministry and fellowship can continue and the congregation's faith is maintained even though it is not optimal. But thank God, this pandemic occurred during a period called the industrial revolution 4.0. The use of this extraordinary technology can be used as a means to mature the congregation as well as to nourish the church so that the desired growth can be achieved properly